Amine and aldehyde functionalized mesoporous silica on magnetic nanoparticles for enhanced lipase immobilization, biodiesel production, and facile separation. (1st May 2021) - Esmi, Fahimeh; Nematian, Tahereh; Salehi, Zeinab; Khodadadi, Abbas Ali; Dalai, Ajay K.
Highlights: Synthesis of magnetic nanoparticles coated with mesoporous silica and functionalization by amine and aldehyde groups. Immobilization of Rhizopus oryzae lipase on the supports via physical adsorption and covalent attachment. Transesterification reaction of olive oil with methanol in the presence of synthesized catalysts. The highest activity and biodiesel yield of aldehyde-functionalized carrier compared to other nanobiocatalysts. Abstract: In this research, synthesis of fatty acid methyl ester (FAME) from olive oil as model feedstock was carried out in the presence of Rhizopus oryzae lipase (ROL) that was immobilized on the mesoporous silica magnetic nanoparticles (MNPs). MNPs were coated with mesoporous silica (MS) functionalized by amine and aldehyde groups used for immobilization of a lipase, used for biodiesel production, and easy magnetic separation of the immobilized lipase from the biodiesel product. MNPs were synthesized by using the co-precipitation method and coated with MS by sol-gel synthesis using cetyltrimethylammonium bromide (CTAB) as a template for mesoporous formation. ROL was immobilized on these supports via physical adsorption and covalent attachment. Enzyme loading efficiency on mesoporous was doubled compared to that on bare MNPs. Also, the covalent bonding led to an increase in enzyme loading from 67.8 to 82.4%. The physico-chemical properties of MNPs were determined by XRD, EDX, VSM, FESEM, BET, and FTIR and were correlated with their activities for biodiesel synthesis. The evaluations of hydrolytic activity and kinetic parameters revealed that MNPs@MS-AP-GA is a suitable nanomaterial for ROL immobilization. Transesterification of olive oil using ROL-MNPs@MS-AP-GA showed the highest biodiesel production of 84.6% among other nanobiocatalysts.